ANALISIS KINERJA KEUANGAN BADAN USAHA MILIK DESA (BUMDES) PODHO JOYO KABUPATEN GRESIK - Endang Malasari; Teti Anggita Safitri (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
Objective: This study aims to determine the financial performance of Village-Owned-Enterprises (BUMDES) based on the ratio of Liquidity, Solvency and Profitability. Methods: The subject of this research was Village-Owned-Enterprises (BUMDES) Podho Joyo in Gresik Regency. The object of this research was the balance sheet and income statement in the financial statements of Village-Owned- Enterprises (BUMDES) Podho Joyo. This study employed a descriptive quantitative approach to determine the financial performance of Village-Owned-Enterprises (BUMDES) Podho Joyo. The data collection techniques were done through interviews, observation and documentation. Results: This study shows that the average liquidity ratio in 2017-2019 measured using the Current Ratio and Quick Ratio has decreased, which means that the performance is not good. The solvency ratio in 2017-2019 as measured using the Debt to Asset Ratio and Debt To Equity Ratio shows a relatively declining result, which means that the performance is not good. The profitability ratios are 2017-2019 as measured using Return On Assets and Return On Equity shows a relatively declining results, which means that their performance is not good. Conclusion: The profit growth every year is very good, but if it is rated from the financial ratios, the financial performance of BUMDES has decreased. This is due to the addition of each business unit that generates profits has decreased financial performance.